Recognizing and Interpreting Personality Types of Senior Secondary School EFL Learners - Zulkifli, Riffat Haqhani; Basikin, Basikin (EDUPEDIA Publisher, 2024)
Language learning comprises comprehensive concept, alongside its components and needs. However, personalities and language learning strategies have been a very intriguing topics for English for Foreign Language (EFL). Language learning have always to be designed as learner- centered, because learners are individuals who differ in significant ways. Personality is the characteristic of someone that influence them in some way of thinking, feeling, and behaving. MBTI type is chosen mainly because its ability to portrays more specifics trait in individuals. MBTI types are divided in four different dimensions, those traits show how individuals’ preference on strategies and techniques on working, such as introvert/extrovert, thinking/feeling, intuitive/sensing, and perceiving/ judging. This review aims to elucidate previous researches on how personality affect English comprehensions among learners. The results showed that on personality traits significantly affect four main categories in EFLLT such as speaking, writing, listening, and reading. Thus, the information can be used in developing EFLLT strategies that can help learners improving their English mastery through the understanding on what is their weakness, strength, and preference